Optimalisasi Produksi Kayu Hutan Alam Melalui Dua Teknik Penebangan - Ningrum, Mutia Herni; Yuniawati, Yuniawati (BRIN Publishing, 2023)
The need for raw materials for logs increases every year but there is not followed by the supply of raw materials for wood from natural forests. Therefore, it is necessary to optimize the production of natural forest wood. This research aims at optimize the production of natural forest logged timber by using two felling techniques. The research method is analyzing data using the simplex linear programming method on POM For Windows 3 software. The research was carried at one forest concession company the IUPHHK-HA in East Kalimantan. The results showed that felling productivity with improved techniques can increased to 3.35 m3/hour and the average cost of production to a minimum of IDR 3,683.91/m3 Felling improved techniques can increase wood production to an optimal of 7.83 m3/tree so that wood production will be obtained by 39.652 m3/day. Each additional productivity input of 1 m3/hour will increase wood production by 0.348 m3/hour. The timber waste from the analysis results is not optimal.